PHYSICIAN/HOSPITAL LIABILITY FOR THE NEGLIGENT REPORTING OR DIAGNOSIS OF CHILD ABUSE JD v East Berkshire Community Health NHS Trust [2005] UKHL 23 - Pieter Carstens (Obiter, 2022)
Medical practitioners, health care practitioners/providers and hospitals are increasingly called upon to make a diagnosis of children who appear to be the victims of sexual or other abuse. Occasionally mistakes are made and such abuse is incorrectly diagnosed, leading to tragic consequences for the child, family and other caregivers. Children may be taken into foster care and parents may suffer psychological trauma and psychiatric illness. Parents or caregivers may even be wrongly accused of such abuse, and consequently tried and convicted on the basis of expert medical evidence. The question arises whether those wrongly accused of such abuse may institute a claim for damages and other relief. It is particularly in the common law jurisdictions that this question has recently surfaced in the context of whether a physician or hospital owes a duty of care to the wrongly accused parent. The English courts in particular have recently been confronted with incorrect/negligent misdiagnoses of child abuse by physicians that have led to the wrongful convictions of a number of appellants who successfully challenged their convictions before the English Courts of Appeal and subsequently had their convictions set aside. Whether physicians in England and Wales owe parents who are wrongly alleged to have abused their children a duty of care in relation to that diagnosis, has now conclusively been dealt with by the English House of Lords in the case of JD v East Berkshire Community Health NHS Trust ([2005] UKHL 23).